Squamapion alpinum n. sp. from Austria (Coleoptera, Apionidae) - Giusto, Carlo (Zootaxa, 2018)
Squamapion alpinum n. sp. from Austria (type locality: Virgen: Marin, Osttirol) is described and figured. It is compared with Squamapion vicinum (Kirby, 1808) and Squamapion atomarium (Kirby, 1808). Clinopodium alpinum (L.) Kuntze (Lamiaceae) is the host plant. A key to European species related to S. vicinum is provided.